I was rereading my Calculus book when I saw this property

For $\displaystyle \alpha \in \mathbb{R} \neq 0 $ and $\displaystyle f:\mathbb{R}^n \rightarrow \mathbb{R} $ a continuously differentiable function.

$\displaystyle \frac{\partial f}{ \partial (\alpha p)} (x) = \alpha \frac{\partial f }{\partial p} (x)$

=====================================

I can see that this property holds true for $\displaystyle \alpha = 1$.

If $\displaystyle \alpha \neq 1 $, then would

$\displaystyle \frac{\partial f }{\partial (\alpha p)}(x) = \sum_{i=1}^{n} \alpha p_{i} \frac{\partial f}{ \partial x_{i}} (x) = \alpha \frac{\partial f }{\partial p} (x) $?

Thank you for your time.